Phase II. - Dickhoff, Wilfried W.; Drechsler, Wolfgang; Gabriel, Gerlinde; Jungwirth, Kurt; Oroschakoff, Haralampi G.; Strobl, Helmut (Graz : Stadtmuseum Graz, 1985)
Baumgarten, Lothar ; Bertocci, Carlo ; Biel, Michael von ; Condo, George ; Dimitrijevic, Braco ; Dokoupil, Jiri Georg ; Federle, Helmut ; Hunger-Bühler, Robert ; Lebrun, Christopher ; De Maria, Nicola ; McKeever, Ian ; Merz, Gerhard ; Merz, Mario ; Oehlen, Albert ; Oroschakoff, Haralampi G. ; Pistoletto, Michelangelo ; Richter, Gerhard ; Salvo ; Schmalix, Hubert ; Schuler, Horst ; Schulze, Andreas ; Trockel, Rosemarie
biog. p. 97-108
Duits
Phase II, Stadtmuseum Graz, Steirischer Herbst Graz, 1985
boek